2015
DOI: 10.1016/j.jneb.2015.04.161
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and Barriers to Limiting Screentime Behaviors by Parents of Preschoolers

Abstract: To examine screentime behaviors and beliefs, barriers to limiting screentime, and methods for coping with barriers of parents of preschool children. Design, Setting and Participants: Parents of preschool children (2 to 5 years old) completed surveys (n¼133); a subset participated in focus group interviews (English-speakers¼16; Spanish-speakers¼14). Constant data comparison occurred concurrently with data collection to establish when data saturation was reached. Outcome Measures and Analysis: Three trained rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Jarvis et al [45] explored barriers that were self-reported by parents through open-ended questions, whereas specific barriers were presented in a self-administered questionnaire to parents in this study. Common barriers encountered by parents in this study (ie, time needed for household chores, weather factor, and coping tools to meet the demand of a busy day) were consistent with previous research findings [23,24,27]. We have found it is a common occurrence among current generations of modern parents to provide screen devices to their young ones as an easy way out [27,46].…”
Section: Principal Findingssupporting
confidence: 87%
See 3 more Smart Citations
“…Jarvis et al [45] explored barriers that were self-reported by parents through open-ended questions, whereas specific barriers were presented in a self-administered questionnaire to parents in this study. Common barriers encountered by parents in this study (ie, time needed for household chores, weather factor, and coping tools to meet the demand of a busy day) were consistent with previous research findings [23,24,27]. We have found it is a common occurrence among current generations of modern parents to provide screen devices to their young ones as an easy way out [27,46].…”
Section: Principal Findingssupporting
confidence: 87%
“…Several studies have demonstrated the role of parental influences on a child's screen time behavior [21,22]. However, it was also reported that parents could be facing various barriers in the efforts to reduce excessive child screen time [23][24][25][26]. Among these barriers were the lack of affordable alternative activities and poor accessibility to them secondary to weather conditions and transportation issues [23,24,26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings suggest that families from disadvantaged contexts may benefit most from public health information highlighting the possible detrimental effects of high screen exposure in infancy. However, it is important to consider the barriers that parents encounter to limiting television including inclement weather, need to have time away from children to complete other activities, parent fatigue, and lack of affordable alternate activities (Martin‐Biggers et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%